2018
DOI: 10.24252/eternal.v41.2018.a8
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Role Play Method Toward Students’ Motivation in English Conversation

Abstract: This study aims to find the effectiveness of role play method toward the students' motivation in English conversation for the first grade students at MTs As'adiyah No. 49 Bola Aserae -Belawa academic year 2016/2017. The method used in this study was quantitative research through pre-experimental method by using one shot case study pre-test and post-test design. Before the treatment, the reseracher did the pretest in one class. Moreover, the researcher taught English conversation by role play technique in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…Penelitian yang dilakukan Wahyudi (2013) dalam meningkatkan karakter dan hasil belajar IPS menggunakan metode bermaen peran pada siswa SD IV Tridadi Kecamatan Sleman, Kabupaten Sleman mengalami peningkatan terhadap hasil belajar siswa. Ini juga didukung dari penelitian Samsibar (2018) dengan judul penelitian The Effectiveness of role play method toward students' motivation in english conversation. Berdasarkan analisis metode role playing mampu memotivasi siswa dalam percakapan Bahasa Inggris.…”
Section: Pendahuluanunclassified
“…Penelitian yang dilakukan Wahyudi (2013) dalam meningkatkan karakter dan hasil belajar IPS menggunakan metode bermaen peran pada siswa SD IV Tridadi Kecamatan Sleman, Kabupaten Sleman mengalami peningkatan terhadap hasil belajar siswa. Ini juga didukung dari penelitian Samsibar (2018) dengan judul penelitian The Effectiveness of role play method toward students' motivation in english conversation. Berdasarkan analisis metode role playing mampu memotivasi siswa dalam percakapan Bahasa Inggris.…”
Section: Pendahuluanunclassified
“…Researchers who study role play such as Samsibar and Naro (2018), Erturk (2015), Glover (2014), and Chesler and Fox (1966) recommend that steps should be followed when engaging students in role play. The SERC document provides three basic steps: the instructor should offer relevant scenarios to students, give students time to complete tasks, and find a way to process students' deliberations (SERC 2018).…”
Section: Role Play As a Teaching Techniquementioning
confidence: 99%
“…The teacher may give students specific instructions or guidance on how to act or what to say (Glover 2014). Samsibar and Naro (2018) used role play to teach students English conversation and to increase their motivation. They found that there was a significant difference in students' motivation to speak English and concluded that role play was effective in improving students' motivation in English conversation.…”
Section: Role Play As a Teaching Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Role-play is a versatile learning activity that allows for diversity and creativity. It incorporates various communicative approaches, enhances language proficiency, promotes classroom participation, and boosts motivation (Kusamana, 2011).…”
Section: Introductionmentioning
confidence: 99%